Identification of suitable solid waste disposal sites using GIS and multi-criteria decision analysis techniques in Burayu Sub City, Oromia region, Ethiopia - Kanenus Fufa Dararo; Gizachew Kabite Wedajo; Siraj Mammo (Discover Environment)
Abstract Inappropriate solid waste dumping presents significant challenges for urban areas in Ethiopia, such as, Burayu Subcity, due to the lack of a proper landfill, posing serious risks to public health and the environment. Hence, this study was conducted to explore the Optimal Suitability sites for solid waste disposal Sites in Burayu Subcity, by integrating Geographic Information System (GIS) and multi-criteria decision-making framework. The study utilized environmental and socio-economic factors as data sources, including land use and land cover, slope, faults, power lines, rivers, roads, settlements, soil data, and water wells (Data types). These factors were weighted to develop a suitability index for landfill siting (data analysis). The data were obtained from the Space Science and Geospatial Institute as well as field surveys (data sources). A multi-criteria evaluation technique using GIS assigned weights to the criteria based on their relative importance, and these weights were integrated to generate a suitability map through overlay analysis. The results revealed that 6% (531 ha), 7% (590 ha), 2% (204 ha), 5% (411 ha), and 80% (6758 ha) of the total study area were found to be highly suitable, suitable, moderately suitable, less suitable, and unsuitable for solid waste landfill sites, respectively. Four suitable landfill sites were identified, all of which meet scientific and environmental criteria. The analysis indicated that the northern, northeastern, southern, and southwestern edges of the Sub city are appropriate locations for sanitary landfills. Currently, the solid waste disposal system in in Study area does not adhere to environmental and scientific standards due to the absence of a properly chosen sanitary landfill. Based on the findings of this study, it is recommended that the Sub city should use these scientifically identified potential landfill sites to ensure sustainable waste management.